Oral administration of Korean perilla frutescens leaf extract shows potential therapeutic effects against COVID-19 in a SH101 hamster model - An, Jin-Soo; Kim, Woong-Il; Hong, Seong-Tshool; Kim, Hae-Mi; Kwon, Oh-Young; Lee, Jae-Hyun; Kim, Young Chul; Lee, Min-Haeng; Kim, Jong-Choon; Song, Si-Whan (Frontiers in Virology, 2025)
Background and objectivesThe outbreak of the COVID-19 pandemic has made the development of effective treatments a critical global issue. This study investigated whether Korean perilla (Perilla frutescens var. frutescens) leaf ethanol extract (P108) showed therapeutic potential against COVID-19 using the SH101 Roborovski hamster model.Materials and methodsThe COVID-19 infection model was established by intranasal administration of SARS-CoV-2 suspension into SH101 Roborovski hamsters. Experimental groups received P108 at dosages of 1,000 and 3,000 mg/kg/day, with additional groups for normal control (no treatment), vehicle control (0 mg/kg/day with vehicle only), and positive control (Paxlovid at 20 mg/kg/day). All substances were administered orally via gavage using a sonde. Treatment effects were assessed by monitoring changes in body temperature, clinical signs, body weight, levels of D-dimer and fibrin degradation products, interleukin concentrations, viral titers, immune cell counts, and lung pathology. Statistical significance was determined for differences with a p-value ≤ 0.05.ResultsHamsters infected with SARS-CoV-2 exhibited typical COVID-19 disease progression, including marked hypoactivity by 4 days post-inoculation (dpi). Both P108- and Paxlovid-treated groups initially developed fever but subsequently recovered, with body weight restoration comparable to the normal control group. At 5 dpi, high-dose P108 and Paxlovid treatment resulted in reduced viral loads in lung tissues. Notably, high-dose P108 demonstrated cytokine modulation and viral load reduction trends similar to those observed with Paxlovid, as detailed in the Results and Figure Legends. P108 treatment significantly lowered fibrin degradation product levels, IL-6, and TNF-α while increasing IL-10. Histological analysis showed reduced pulmonary inflammation in the P108-treated groups.ConclusionThe results of this study suggest that P108 may inhibit SARS-CoV-2 replication and reduce systemic inflammatory responses. These findings support the continued development of P108 as a candidate for preventive or early-intervention strategies against COVID-19. However, its efficacy following delayed treatment initiation (e.g., after symptom onset) has not yet been demonstrated and warrants further investigation.